The Impact of Business Analytics on Collaborative Advantage: the mediating role of managing transaction costs - Letícia de Sousa Milhomem; Larissa Alves Sincorá; Marcos Paulo Valadares de Oliveira; Marcelo Moll Brandão (BBR: Brazilian Business Review)
The objective of the research was to verify the existence of the mediating role of Transaction Cost Management (TCM) in the relationship between Business Analytics (BA) and Collaborative Advantage (CA). Based on a quantitative approach, it was found that there is a partial mediation exercised by the TCM in the relationship between BA and CA. In addition, the results showed that the tested model was able to explain 69,30% of the CA variation. The article goes on to deepen the theoretical relationships between the variables that make up the research model, cooperating both for the evolution of the emerging field in BA, and for a reflection on the critical success factors of the organizational alliances. Furthermore, based on the proposed model, it is possible to revisit the Transaction Costs Theory, discussing its assumptions in the current scenario marked by the high production of data and information in corporations, suggesting that business analytics is a directly influencing element in management of transaction costs.